WHO AVOID TAXES? AN EMPIRICAL STUDY FROM THE CASE OF INDONESIA - Satyadini, Agung Endika; Erlangga, Restu Rea; Steffi, Brigitta (Scientax, 2019)
This paper investigated the propensity and the magnitude of tax avoidance risk exposure among different taxpayers by analyzing both enterprise-related and government-related variables. Providing far-reaching analysis and examining a relatively unexplored area of conforming tax avoidance, this study employs two measurements of tax avoidance including non-conforming and conforming tax avoidance. In the brain area of empirical analysis, this paper combined a fixed-effect model to control omitted variable bias together with adoption of heteroskedasticity and autocorrelation-consistent standard errors (HAC/clustered SE). The results depict that the magnitude of tax avoidance risks varies depending on the characteristics of taxpayers. Higher risks were found in so-called foreign-controlled enterprises and foreign invested enterprises. With respect to entities’ sector, this study also demonstrates that the propensity of higher risk exposure was depicted in financial and mining sector relative to full sample taxpayers.